Sex-Differences in Aortic Stenosis: Mechanistic Insights and Clinical Implications - Matilla, Lara; Garaikoetxea, Mattie; Arrieta, Vanessa; García-Peña, Amaia; Fernández-Celis, Amaya; Navarro, Adela; Gainza, Alicia; Álvarez, Virginia; Sádaba, Rafael; Jover, Eva; López-Andrés, Natalia (Frontiers in Cardiovascular Medicine, 2022)
Objective: We aim to analyse sex-specific differences in aortic valves (AVs) and valve interstitial cells (VICs) from aortic stenosis (AS) patients. Approach and Results: 238 patients with severe AS undergoing surgical valve replacement were recruited. 202 AVs (39.1% women) were used for ex vivo analyses and 36 AVs (33.3% women) for in vitro experiments. AVs from men presented increased levels of the inflammatory molecules interleukin (IL)-1b, IL-6, Rantes and CD45. Oxidative stress (eNOS, myeloperoxidase, malondialdehyde and nitrotyrosine) was upregulated in male AVs. Concerning fibrosis, similar levels of collagen type I, decreased levels of collagen type III and enhanced fibronectin, active Lox-1 and syndecan-1 expressions were found in AVs from men compared with women. Extracellular matrix (ECM) remodelling was characterized by reduced metalloproteinase-1 and 9 expression and increased tissue inhibitor of metalloproteinase-2 expression in male AVs. Importantly, osteogenic markers (bone morphogenetic protein-9, Rank-L, osteopontin, periostin, osteocalcin and Sox-9) and apoptosis (Bax, Caspase 3, p53 and PARP1) were enhanced in AVs from men as compared to women. Isolated male VICs presented higher myofibroblast-like phenotype than female VICs. Male VICs exhibited increased inflammatory, oxidative stress, fibrotic, apoptosis and osteogenic differentiation markers. Conclusions: Our results suggest that the mechanisms driving the pathogenesis of AS could be different in men and women. Male AVs and isolated VICs presented more inflammation, oxidative stress, ECM remodelling and calcification as compared to those from women. A better knowledge of the pathophysiological pathways in AVs and VICs will allow the development of sex-specific options for the treatment of AS.